Post-Event Reflection: A Tool to Facilitate Self-Awareness, Self-Monitoring, and Self-Regulation in Athletes. Issue 2 (3rd April 2019) - Chow, Graig M.; Luzzeri, Matteo
Abstract: The underlying basis of many psychological interventions is self-awareness. Systematic self-reflection enhances self-awareness, which improves self-monitoring, self-correction, and ultimately self-regulation (Kirschenbaum, 1997 ). Theoretically, the capability to self-reflect following performance has motivational, cognitive, and behavioral effects (Ellis, Carette, Anseel, & Lievens, 2014 ), increases intrinsic motivation, and results in more internal and controllable attributions (Allen, Jones, & Sheffield, 2010 ). This paper introduces a tool—the Post-Event Reflection (PER)—that practitioners can use to assist athletes in processing their performances in a productive, improvement-focused manner. The PER's conceptual and empirical rationale, practical implementation and implications, benefits, and challenges are presented.